Advancing Supply Chain Resilience Through Cloud-Based Logistics: A Narrative Review - Judijanto, Loso; Zulfikri, Agung (Sinergi International Journal of Logistics, 2024)
The digital transformation of global supply chains has accelerated the adoption of cloud-based logistics systems. This study presents a narrative review that explores the architecture, benefits, and implementation challenges of cloud logistics. Drawing on literature from Scopus, IEEE Xplore, and Google Scholar, it analyzes empirical and conceptual findings from multiple sectors and geographic contexts. Results reveal that hybrid cloud architectures, IoT integration, and modular microservices enhance logistics efficiency, transparency, and responsiveness. Real-time tracking, predictive analytics, and stakeholder collaboration emerge as key performance enablers. However, implementation is hindered by data security concerns, inadequate infrastructure, poor system interoperability, and human resource limitations. These challenges are more pronounced in developing regions and among small enterprises. The discussion links these findings to supply chain theory, highlighting the role of systemic factors such as policy, digital infrastructure, and organizational culture. It emphasizes the need for supportive government policies, investment in IT infrastructure, and workforce training as critical strategies for overcoming barriers. The study also identifies gaps in the literature related to regional disparities and long-term impact assessments. It recommends future research on integrated frameworks that combine technical, organizational, and policy perspectives. The findings underscore the importance of a holistic, collaborative approach to realize the full potential of cloud-based logistics in building adaptive and resilient supply chains.